The Main Character’s Personality in Daniel Keyes’ Flowers for Algernon - Susi Astiantih; Yetty (Hasanuddin University, 2021)
Flowers For Algernon, a novel by Daniel Keyes, is one of his most renowned literary works. It had won Nebula and Hugo awards. The story centers on Charlie, a 32-year-old man with a debilitating mindset who undergoes surgery to boost his IQ. The goal of this research is to elucidate the main character's description in Flowers for Algernon. The writer utilized a structural technique to analyze Daniel Keyes' more deeply since this method exposes as precisely, as thoroughly, as precisely, and as deeply as possible the connections and entanglement of all parts and aspects of literary works. The study demonstrates that each human being is born with unique characteristics, abilities, and impairments. Additionally, individuals should embrace who they are and be themselves, even though most of them seek to alter various parts of their lives.